Metsärajan muutokset Lapissa 1983-2009 - Huhta, Esa; Franke, Anna K.; Aatsinki, Pasi; Hallikainen, Ville; Hyppönen, Mikko; Juntunen, Vesa; Mikkola, Kari; Neuvonen, Seppo; Rautio, Pasi
Tutkimusseloste Seloste artikkelista: Franke A.K., Aatsinki P., Hallikainen V., Huhta E., Hyppönen M., Juntunen V., Mikkola, K., Neuvonen S., Rautio, P. (2015). Quantifying changes of the coniferous forest line in Finnish Lapland during 1983–2009. Silva Fennica vol. 49 no. 5 article id 1408. http://dx.doi.org/10.14214/sf.1408 2016